THE EFFECT OF GREEN SUPPLY CHAIN MANAGEMENT PRACTICES ON CONSUMER WILLINGNESS TO PAY MORE: AN ANALYSIS OF THE ROLE OF MEDIATION AND MODERATION - Hadist Fadhillah; Wahyuningsih Santosa; Dorina Widowati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of green supply chain management practices on consumers' willingness to pay more by considering the mediating role of consumer-perceived product performance and the moderating role of consumers' moral orientation towards the environment. The background of this study is based on increasing public concern about sustainability issues and high consumer demand for more environmentally friendly business practices, particularly in the coffee shop industry in Jakarta. The research method used a quantitative approach with a purposive sampling technique, involving 289 respondents from Generation Z and Millennials who had purchased products from coffee shops implementing green supply chain management practices. The results showed that green supply chain management practices positively influenced consumers' willingness to pay more and perceived product performance. Product performance was also shown to increase willingness to pay more and mediate the relationship between green supply chain practices and willingness to pay more. However, consumers' moral orientation towards the environment did not moderate either relationship. These findings emphasize the importance of optimizing green supply chain practices to increase product value while encouraging consumers' willingness to pay more.